2011
DOI: 10.1111/j.1365-2516.2011.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood rotation thromboelastometry (ROTEM®) in nine severe factor V deficient patients and evaluation of the role of intraplatelets factor V

Abstract: Severe factor V (FV) deficiency (parahaemophilia) is a rare congenital hemorrhagic disorder characterized by very low or undetectable plasma FV levels and bleeding phenotype ranging from mild to severe. We evaluated whole blood (WB) rotation thromboelastometry (ROTEM) in parahaemophilia patients and the contribution of intraplatelets FV, if any, to clot formation. Standard ROTEM(®) assays were performed in WB from nine parahaemophilia patients and 50 healthy controls. In addition, platelets poor plasma from on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Tests evaluating global hemostatic capacity (thrombin generation test and thromboelastography) may provide more accurate evaluation of in vivo hemostasis and treatment response and be better suited to predict clinical phenotype as they more effectively assess rate/total thrombin generated, whole blood clot formation, and/or fibrin polymerization. Recently, these tests have been used to evaluate hemostasis in patients with RBDs, 30,31 specifically FV 32,33 and FXI 34 deficiency. These assays represent an emerging strategy to determine therapeutic effectiveness and to monitor RBD treatment, particularly FXI deficiency where standard assays fail to correlate with bleeding risk.…”
Section: Global Hemostasis Testsmentioning
confidence: 99%
“…Tests evaluating global hemostatic capacity (thrombin generation test and thromboelastography) may provide more accurate evaluation of in vivo hemostasis and treatment response and be better suited to predict clinical phenotype as they more effectively assess rate/total thrombin generated, whole blood clot formation, and/or fibrin polymerization. Recently, these tests have been used to evaluate hemostasis in patients with RBDs, 30,31 specifically FV 32,33 and FXI 34 deficiency. These assays represent an emerging strategy to determine therapeutic effectiveness and to monitor RBD treatment, particularly FXI deficiency where standard assays fail to correlate with bleeding risk.…”
Section: Global Hemostasis Testsmentioning
confidence: 99%
“…We estimated that it would be safe to remove the epidural catheter after transfusion of three units of platelets, but a prior case report that describes the cessation of hematuria in a patient with factor V deficiency after only one unit of platelet suggests that even one unit of platelets might be adequate for hemostasis. Although our institution does not have the platelet factor V assays previously described, thromboelastography or thromboelastometry, these tests could potentially offer better guidance to management rather than quantitative plasma factor V levels . It is probable that not all parturients with factor V deficiency require a minimum plasma factor V level of 50% for epidural catheter placement, and in the case of platelet transfusion, plasma factor V levels are unlikely to offer any meaningful guidance.…”
Section: Discussionmentioning
confidence: 99%
“…4 Patients with congenital factor V deficiency have variable degrees of bleeding that does not correlate with plasma factor V levels. 5 In patients with congenital factor V deficiency, the abnormality seen in whole blood coagulation using ROTEM ® was described by Spiezia et al 6 The authors found that the time required to initiate clotting, CT, was markedly prolonged, as expected for extrinsic and intrinsic pathway activators. However, once coagulation was initiated, the rate of clotting (CFT), the α-angle and the maximum degree of fibrin formation (MCF) were normal.…”
Section: Importance Of Platelet Activation In the Regulation Of Wholementioning
confidence: 96%
“…However, once coagulation was initiated, the rate of clotting (CFT), the α-angle and the maximum degree of fibrin formation (MCF) were normal. 6 This suggests that plasma factor V is critical for initiating the formation of thrombin and promotes platelet-dependent thrombin formation that accelerates fibrin formation. In addition, the authors found that the addition e308 | LETTER TO THE EDITOR of normal platelets shortened the time required to initiate clotting, demonstrating the importance of platelet factor V release in initiating thrombin generation.…”
Section: Importance Of Platelet Activation In the Regulation Of Wholementioning
confidence: 99%
See 1 more Smart Citation